Internationalization of Education during the Epoch of COVID-19 Pandemic: the way forward - Ahmad H.Osman, Rahmah; Subramaniam, Vijayaletchumy; Zakariyah, Luqman; Arumugom, Vijayasegaran (2021)
The COVID-19 global pandemic has imposed many new but grave challenges in the field of education. Researchers have taken the next step to study on ways to resolve the myriad problems created by this sudden shift caused by the global pandemic. This paper reviews the many impacts of COVID-19 on internationalization, focusing on the challenges in the education field such as international student mobility, closure of campuses, enrolment for international education and classroom teaching-learning delivery. In addition to that, this paper signifies the challenges of internationalization during the Covid-19 pandemic. The paper concludes that the mobility of students is essential in reaching the peak of internationalization.